With a little help from my website: Firm survival and web presence in times of COVID-19 - Evidence from 10 European countries - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2021)
This paper uses firm level data from the World Bank Enterprise surveys conducted in 2019 and from the COVID-19 follow-up surveys conducted in 2020 in ten European countries to investigate the link between having a website before the pandemic and firm survival until 2020 .The estimated effect of web presence is statistically highly significant ceteris paribus after controlling for various firm characteristics that are known to be related to survival. Furthermore, the size of this estimated effect can be considered to be large on average. A web site helped firms to survive.
Keywords: D22; L20; L25; L29; 330; web presence; firm survival; COVID-19; World Bank Enterprise Surveys